COVID-19 is a Global Threat, But Why Mucormycosis upsurged in India Alone? - Tom, Antriya Annie; Kareem, Sulaikha Abdul; Jojo, Chrins Thomas (Journal of Pharmacy Practice and Community Medicine)
A fatal problem associated with SARS-CoV-2 called mucormycosis or black fungus was observed in COVID-19 patients worldwide, in particular from India. The rare infection rose more rapidly during the second wave of COVID in India. Upswing in mucormycosis is a public health concern as the fatality rate is pretty high, upto 90%. These realities demanded a search for the reason for upsurging cases of mucormycosis in India alone. The probable explanations for COVID patients developing mucormycosis include injudicious use of steroids, uncontrolled diabetes with or without diabetic ketoacidosis (DKA), absurd use of immuno-modulants with steroids, and extensive use of antimicrobials. Besides, overuse of zinc and iron supplements, features of B.1.617 variant of SARS-CoV-2 that suppress immunity, along with several other risk factors including long intensive care unit (ICU) stays with or without mechanical ventilators might have contributed to the increased prevalence of mucormycosis in patients with COVID-19. India is regarded as the “mucor capital of the world”, having 70 times higher pre-COVID incidence than the global data. Therefore, it is vital to rectify the aggravating factors and curb the spread of mucormycosis. If this isn’t brought under control, there are chances of other deadly infections to remain in the background. Rational glycemic control in COVID patients should be ensured. Use of steroids and immuno-modulants along with steroids should be reserved. Also, use of immunity boosters like zinc and iron should be limited. Furthermore, a holistic approach to improve the use of selfmedication through public education should be introduced. Government should make sure that the oxygen cylinders are hygienic and rightly maintained. Sterile normal saline or distilled water should be used in humidifiers and oxygen flow meters has to be changed periodically. Negligence of all these imparts a huge mess not only on individuals but also on government. If the tribulations of overuse of drugs and insufficient hygiene persist, chances of outbreak of secondary infections alongside epidemics and pandemics should be expected in future.
Keywords: Mucormycosis; Blackfungus; COVID-19; India; Infection